VASYL STEFANYK’S РROSE POEM «FOR OLGA»: TEXT HISTORY - Varchuk, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The paper deals with textual studying of Vasyl Stefanyk’s prose poem «For Olga». On the basis of detail analysis of epistolary texts and handwritten sources there were given some practical recommendations concerning the publication of this prose poem in the framework of the oncoming critical edition.